The history, genome and biology of NCTC 30: a non-pandemic Vibrio cholerae isolate from World War One. Issue 1900 (10th April 2019) - Dorman, Matthew J.; Kane, Leanne; Domman, Daryl; Turnbull, Jake D.; Cormie, Claire; Fazal, Mohammed-Abbas; Goulding, David A.; Russell, Julie E.; Alexander, Sarah; Thomson, Nicholas R.
Abstract : The sixth global cholera pandemic lasted from 1899 to 1923. However, despite widespread fear of the disease and of its negative effects on troop morale, very few soldiers in the British Expeditionary Forces contracted cholera between 1914 and 1918. Here, we have revived and sequenced the genome of NCTC 30, a 102-year-old Vibrio cholerae isolate, which we believe is the oldest publicly available live V. cholerae strain in existence. NCTC 30 was isolated in 1916 from a British soldier convalescent in Egypt. We found that this strain does not encode cholera toxin, thought to be necessary to cause cholera, and is not part of V. cholerae lineages responsible for the pandemic disease. We also show that NCTC 30, which predates the introduction of penicillin-based antibiotics, harbours a functional β-lactamase antibiotic resistance gene. Our data corroborate and provide molecular explanations for previous phenotypic studies of NCTC 30 and provide a new high-quality genome sequence for historical, non-pandemic V. cholerae .